2
$\begingroup$

Let $A:D(A)\longrightarrow H$ be an unbounded self-adjoint (or normal) operator on a Hilbert space $H$. Then we know that $\sigma(A) \neq \emptyset$ and $$\|(\lambda-A)^{-1}\|=\frac{1}{d(\lambda,\sigma(A))}, \quad \forall \lambda \in \rho(A),$$ where $d(\lambda,\sigma(A))=\min_{\mu \in \sigma(A)} |\lambda-\mu|>0$. Do we have a similar formula for $$\|A(\lambda-A)^{-1}\|= ?$$ I point out that $A(\lambda-A)^{-1}$ is a bounded operator since $A(\lambda-A)^{-1}x=-x+\lambda(\lambda-A)^{-1}x$ for any $x \in H$. I have the basic estimate $$\|A(\lambda-A)^{-1}\| \leq 1+\frac{|\lambda|}{d(\lambda,\sigma(A))}.$$ Is it sharp ?

$\endgroup$
3
$\begingroup$

The following is exact: $$ \|A(\lambda I-A)^{-1}\|=\sup_{\mu\in\sigma(A)}\left|\frac{\mu}{\lambda-\mu}\right| % \\ = \sup_{\mu\in\sigma(A)}\left|-1+\frac{\lambda}{\lambda-\mu}\right|. $$ If $\sigma(A)=\mathbb{R}$ and $\lambda=i$, then the above gives $$ \|A(\lambda I-A)^{-1}\| = \sup_{\mu\in\mathbb{R}}\frac{|\mu|}{\sqrt{\mu^2+1}} =1. $$ while your expression gives $$ 1+\frac{1}{1}=2. $$

$\endgroup$
  • $\begingroup$ Thanks for you answer. Do you use the spectral theorem for self-adjoint operators to prove it ? If so, do you have a more elementary proof (similar to the one to establish the expression for $\|(\lambda-A)^{-1}\|$) ? $\endgroup$ – perturbation Jan 10 '18 at 22:20
  • $\begingroup$ @perturbation : I was working from the spectral theorem. Trying to do this directly would be a little tedious, but it should be possible. $\endgroup$ – DisintegratingByParts Jan 10 '18 at 23:18
  • $\begingroup$ Ok thank your for your help. $\endgroup$ – perturbation Jan 11 '18 at 6:56
1
$\begingroup$

Actually, I have found a simple answer in the bible Kato (1966), p. 277 identities (3.31). The proof is the same as for the bounded case, to which Kato refers (see (3.17), p. 273). I reproduced the arguments below for the sake of completeness.

Recall that $A(\lambda-A)^{-1}=-Id+\lambda(\lambda-A)^{-1}$. Since $A$ is normal, the bounded operator $B=-Id+\lambda(\lambda-A)^{-1}$ is normal. Therefore, we have the know fact that $$\|B\|=\sup_{\eta \in \sigma(B)} |\eta|.$$ Since $\sigma(B)=\sigma(-Id+\lambda(\lambda-A)^{-1})=f(\sigma(A))$ with $f(\mu)=-1+\frac{\lambda}{\lambda-\mu}$, we have $$ \begin{array}{rl} \|A(\lambda-A)^{-1}\| &=\sup_{\eta \in \sigma(A(\lambda-A)^{-1})} |\eta| \\ &=\sup_{\eta \in f(\sigma(A))} |\eta| \\ &=\sup_{\mu \in \sigma(A)} |f(\mu)| \\ &=\sup_{\mu \in \sigma(A)} |-1+\frac{\lambda}{\lambda-\mu}| \\ &=\sup_{\mu \in \sigma(A)} |\frac{\mu}{\lambda-\mu}| \end{array}. $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.